2016
DOI: 10.1186/s12610-016-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Leydig cell tumor of the testis with azoospermia and elevated delta4 androstenedione: case report

Abstract: BackgroundSecreting interstitial cell (Leydig cell) tumors are rare. In adults, the clinical picture and steroid levels are variable.Case presentationThis paper presents a case of left testicular tumor, showing azoospermia with normal serum level of total testosterone, collapsed FSH and LH, and high delta4 androstenedione. Histopathological investigation revealed a Leydig cell tumor. TESE allowed spermatozoa extraction and freezing. Testicular histology found hypospermatogenesis and germ-cell aplasia with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Recently, an article reported a case of unilateral orchiectomy with synchronous TESE in a patient with elevated delta 4 androstenedione and suppressed LH and FSH . Fortunately, the couple achieved a natural pregnancy because of spermatogenesis recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an article reported a case of unilateral orchiectomy with synchronous TESE in a patient with elevated delta 4 androstenedione and suppressed LH and FSH . Fortunately, the couple achieved a natural pregnancy because of spermatogenesis recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a case report of a patient with azoospermia who also had normal testosterone and suppressed gonadotropins was reported. However, this patient had high androstenedione levels, and pathology showed a Leydig cell tumor [9]. Another case report described a patient with a malignant Leydig cell tumor who presented with normal testosterone together with low LH and FSH.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is considered the initial investigative method for the diagnosis of LCT and shows hypoechoic mass with a heterogeneous enhancement pattern or peripheral hypervascularity. [ 11 , 14 , 15 ] With high tissue resolution, MRI seems to be superior to ultrasonography in demonstrating the testicular lesions. [ 16 ] By comparing MRI findings in 104 patients with different testicular pathologies, Fernandez et al [ 17 ] concluded that “marked and maintained enhancement” was the characteristic sign of LCT in differentiation from other testicular tumors.…”
Section: Discussionmentioning
confidence: 99%